2021
DOI: 10.1108/bjm-08-2020-0276
|View full text |Cite
|
Sign up to set email alerts
|

How does Schwartz's theory of human values affect the proenvironmental behavior model?

Abstract: PurposeThe diversity of perspectives means that one can find many factors and models of proenvironmental behavior. However, they typically suffer from limitations and varying degrees of validity in specific contexts, suggesting that today the prime goal should be to learn and improve the models which have been already developed. In this study, the authors build on the model for predicting proenvironmental behavior developed by Oreg and Katz-Gerro (2006), namely one of the most comprehensive cross-national proe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Some scholars (e.g. Primc et al. , 2021; Zientara and Zamojska, 2018) claim, for instance, that environmental values directly affect the engagement in PEB.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Some scholars (e.g. Primc et al. , 2021; Zientara and Zamojska, 2018) claim, for instance, that environmental values directly affect the engagement in PEB.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Environmental concern was not affected, and thus hypothesis H_04 had to be rejected. While the influence of openness to change on perceived risk can be explained by the fact that people with a high appreciation for openness are more likely to be assigned to the anxiety-free individuals who perceive risk less strongly, the lack of influence on environmental concern is contrary to, e.g., (Primc et al, 2021), whose research linked self-direction to environmental concern. An explanation can be taken from the theory that assigns openness to change to the personal rather than the social hemisphere (Cieciuch & Schwartz, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They are interested not only in their own concerns but also in the environment. Primc, Ogorevc, Slabe‐Erker, Bartolj, and Murovec (2021, p. 287) found that self‐direction had a positive influence on environmental concern. Therefore, we expect a negative influence of openness on perceived risk and a positive effect on environmental concern, and we develop the following hypotheses:…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The multiplicity of definitions is a result of the fact that in many areas value has a different meaning and concerns a different conceptual scope. One of the definitions of values existing in psychology is Schwartz's approach, which assumes that values are concepts or beliefs about desirable goals that describe specific states of affairs or behaviour (Primc et al, 2021). For the human, values are ordered by importance.…”
Section: Values In Marketing (Materials and Non-material)mentioning
confidence: 99%